Impact of the parent training program on parental competences and children quality of life in Cape Verde - Correia, Adriana (2024)
The Family-Based Preventive Intervention (FAF) is a program designed with the aim of promoting positive parenting and preventing child maltreatment. This work objective is to describe some of the preliminary data and its implementation on families at psychosocial risk in Boavista Island in Cape Verde, and to analyse its efficacy in the field of parenting’ competence and children's quality of life. The FAF was dynamized in 12 group sessions, with experiential and participatory methodologies, on a weekly basis, for four months. 66 parents participated, mostly mothers (85%), aged between 26 and 56 years (M = 35.53; SD = 7.27), divided into two groups (intervention and control). The evaluation was carried out in the pre- and post-test, for both groups, measuring parenting competence and children's quality of life. The intervention group significantly improved their post-intervention scores on perceived efficacy, parental satisfaction, and children's quality of life, with a moderate effect size. The control group did not show significant differences between moments. We can conclude that the FAF program is a psychoeducational intervention that promotes feelings of parental efficacy and parental satisfaction, which can produce better results for child development and well-being in families at psychosocial risk.